A qualitative study exploring health perceptions and factors influencing participation in health behaviors in colorectal cancer survivors. Issue 2 (3rd March 2016) - Hardcastle, Sarah J.; Maxwell‐Smith, Chloe; Zeps, Nik; Platell, Cameron; O'Connor, Moira; Hagger, Martin S.
Abstract: Purpose: The purpose of the study was to explore colorectal cancer survivors' health perceptions following cessation of active treatment for cancer and to explore the factors influencing participation in health‐promoting behaviors that may help reduce cardiovascular disease risk. Methods: Face‐to‐face interviews were conducted with participants that had completed active treatment for cancer within the previous 2 years. Participants were colorectal cancer survivors ( N = 24, men = 11, women = 13, M age = 69.38 years, SD = 4.19) recruited from a private hospital in Perth, Australia on the basis that they had existing morbidities that put them at increased risk of cardiovascular disease. Interview transcripts were analyzed using thematic analysis. Results: Five main themes emerged: back to normal ; the pleasures in life: 'is it worth it?'; beliefs about health behavior; skepticism of eating guidelines; and lack of motivation. The majority of participants felt they were in good health and had made a full recovery. Participants questioned whether it was worth changing their lifestyle given their life stage and referred to the desire to enjoy life. Lay health beliefs, skepticism of eating guidelines, and a lack of motivation were barriers to change. Conclusions: Interventions should target lay beliefs and skepticism in relation to health behaviors in order to reinforce the importance and value of participating in health‐related behavior. Implications for Cancer Survivors: Findings may inform the development of effective, patient‐centered interventions that target lay health beliefs and build motivation for health behavior change. Copyright © 2016 John Wiley & Sons, Ltd.